2006
DOI: 10.1161/circulationaha.105.001214
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role of Extracellular Nucleotides in Valve Calcification

Abstract: Background-Calcific aortic valve disease is a common condition and is associated with inflammatory changes and expression of osteoblast-like cell phenotypes, but the cellular mechanisms are unclear. Recent studies identified extracellular ATP and P2Y receptor cascade as important regulators of bone remodeling, whereas its breakdown product, adenosine, is known to have anti-inflammatory properties. We hypothesize that extracellular ATP and adenosine have important roles in regulating osteoblast differentiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 19 publications
2
45
0
Order By: Relevance
“…In contrast, adenosine treatment reduced the activity alkaline phosphatase in human valve interstitial cells cultures in osteogenic media. [7] These findings suggest that changes in the activities that convert ATP to adenosine and then degrade adenosine to inosine could have impact on susceptibility of the valve for pathologies such as calcification and underlies the importance of observations made in present study. A new inherited disorder of nucleotide metabolism causing complete loss of e5NT activity has recently been described.…”
Section: Discussionsupporting
confidence: 70%
“…In contrast, adenosine treatment reduced the activity alkaline phosphatase in human valve interstitial cells cultures in osteogenic media. [7] These findings suggest that changes in the activities that convert ATP to adenosine and then degrade adenosine to inosine could have impact on susceptibility of the valve for pathologies such as calcification and underlies the importance of observations made in present study. A new inherited disorder of nucleotide metabolism causing complete loss of e5NT activity has recently been described.…”
Section: Discussionsupporting
confidence: 70%
“…First we found CD73 activity among the highest in the human body [10,46]. Furthermore, we found that human valve interstitial cells could be shifted toward osteoblast phenotype with high alkaline phosphatase activity by exposure to ATP or non-hydrolizable ATP analog while exposure to adenosine block this transformation [47].…”
Section: Cd73 and Arterial Calcificationsmentioning
confidence: 75%
“…Other studies have shown that increased inflammatory markers are attributed to shared risk factors with cardiovascular disease and infiltration of lipoproteins and interstitial cells (16,17). Inhibition of the inflammatory activation, possibly by statins (18,19) although not demonstrated in the current study, might be a beneficial pharmacological prevention of AVS. Study limitations.…”
Section: Discussionmentioning
confidence: 62%